2010
DOI: 10.3109/00365548.2010.513066
|View full text |Cite
|
Sign up to set email alerts
|

Oral vancomycin may have significant absorption in patients with Clostridium difficile colitis

Abstract: A patient on haemodialysis with bowel ischemia was given vancomycin 500 mg orally every 6 h for superimposed Clostridium difficile colitis resulting in a high vancomycin serum concentration. When treating C. difficile colitis in patients with significant renal impairment and bowel injury, we recommend administering the lower dose of oral vancomycin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Vancomycin toxicity has been observed in isolated cases where reduced colonic barrier function and poor clearance of absorbed vancomycin were suspected [26]. There have also been reports of appreciable circulating levels of vancomycin following oral administration without apparent toxicity in patients with or without CKD [27]. Other investigations found no evidence of absorption in patients with severe CDI and/or CKD [28].…”
Section: Discussionmentioning
confidence: 99%
“…Vancomycin toxicity has been observed in isolated cases where reduced colonic barrier function and poor clearance of absorbed vancomycin were suspected [26]. There have also been reports of appreciable circulating levels of vancomycin following oral administration without apparent toxicity in patients with or without CKD [27]. Other investigations found no evidence of absorption in patients with severe CDI and/or CKD [28].…”
Section: Discussionmentioning
confidence: 99%
“…Vancomycin dose above 125 mg four times daily is not routinely recommended, recent reports suggesting no improvement in clinical cure, mortality or complications with increasing dose in severe disease . Reports of high serum vancomycin levels with 500 mg four times day dosing have also been noted in patients . Intravenous vancomycin therapy is not effective in CDI, however, colonic administration through an enema may be effective as an adjunctive therapy (uncertain dosing) if oral therapy is unable to be tolerated (500 mg in 100 mL normal saline, rectally 6 hourly) …”
Section: What Antibiotics Should Be Used For Treatment Of An Initial mentioning
confidence: 99%
“…69 Reports of high serum vancomycin levels with 500 mg four times day dosing have also been noted in patients. [70][71][72] Intravenous vancomycin therapy is not effective in CDI, however, colonic administration through an enema may be effective as an adjunctive therapy (uncertain dosing) if oral therapy is unable to be tolerated (500 mg in 100 mL normal saline, rectally 6 hourly). 4,[73][74][75] Recommendations 1.…”
Section: Dosing and Administrationmentioning
confidence: 99%
“…While renal impairment has been reported to be a risk factor for elevated serum VCM concentrations during enteral or oral administration in some cases (6, 7), it has also been reported that a patient with normal renal function developed significant absorption of oral VCM (5). Theoretically, renal impairment should be a risk factor in elevation of serum VCM concentration.…”
Section: Discussionmentioning
confidence: 99%